Timing of Pregnancy After Kidney Transplantation and Risk of Allograft Failure. Issue 8 (4th April 2016) - Rose, C.; Gill, J.; Zalunardo, N.; Johnston, O.; Mehrotra, A.; Gill, J. S.
Abstract : The optimal timing of pregnancy after kidney transplantation remains uncertain. We determined the risk of allograft failure among women who became pregnant within the first 3 posttransplant years. Among 21 814 women aged 15–45 years who received a first kidney‐only transplant between 1990 and 2010 captured in the United States Renal Data System, n = 729 pregnancies were identified using Medicare claims. The probability of allograft failure from any cause including death (ACGL) at 1, 3, and 5 years after pregnancy was 9.6%, 25.9%, and 36.6%. In multivariate analyses, pregnancy in the first posttransplant year was associated with an increased risk of ACGL (hazard ratio [HR]: 1.18; 95% confidence interval [CI] 1.00, 1.40) and death censored graft loss (DCGL) (HR:1.25; 95% CI 1.04, 1.50), while pregnancy in the second posttransplant year was associated with an increased risk of DCGL (HR: 1.26; 95% CI 1.06, 1.50). Pregnancy in the third posttransplant year was not associated with an increased risk of ACGL or DCGL. These findings demonstrate a higher incidence of allograft failure after pregnancy than previously reported and that the increased risk of allograft failure extends to pregnancies in the second posttransplant year. Abstract : This study demonstrates a higher incidence of kidney allograft failure after pregnancy than previously reported, and the increased risk of allograft failure extends to pregnancies in the second year posttransplant.